1995
DOI: 10.1002/cnm.1640110708
|View full text |Cite
|
Sign up to set email alerts
|

Improved element stresses for node and element patches using superconvergent patch recovery

Abstract: SUMMARYMethods to calculate improved postprocessed stresses in elements for the superconvergent patch recovery technique are developed. Based on improved stresses on node patches, the improved element stresses are obtained by using weighting of patch solutions from different patch assembly points. An alternative method is to directly calculate the element stresses for an element patch based on weighted information. Numerical examples show that the performances of the two procedures are of about the same qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In Reference 5, the displacement ®eld was interpolated instead of stress, and thus essential boundary residuals were required to be added to the least square functional. Wiberg et al 6 also presented a stress based element patch with quadratic weight functions for QUAD4 elements and showed that the extracted results compared to that in Reference 3. In addition to these, Wiberg and Li 7 also published a displacement ®eld based extraction process which was essentially almost similar to the work in Reference 5.…”
Section: Introductionmentioning
confidence: 84%
“…In Reference 5, the displacement ®eld was interpolated instead of stress, and thus essential boundary residuals were required to be added to the least square functional. Wiberg et al 6 also presented a stress based element patch with quadratic weight functions for QUAD4 elements and showed that the extracted results compared to that in Reference 3. In addition to these, Wiberg and Li 7 also published a displacement ®eld based extraction process which was essentially almost similar to the work in Reference 5.…”
Section: Introductionmentioning
confidence: 84%
“…Whenever they are not satisfied, a regularization term is added to the least square functional presented in Section 3.3.2 and Eq. (27). The value of the β coefficient of (27) is iteratively increased till the constraints of (29) are satisfied.…”
Section: Engineering Issuementioning
confidence: 99%
“…On the other hand, in a Lagrangian formulation with complete remeshing, some parts of the domain are very often only weakly changed by remeshing. Therefore, in order to minimize diffusion resulting from usual transfer techniques, interpolation can be avoided through a direct calculation of recovered fields on element patches, as for instance in [27,29]. Element patches, P g , are built on the old mesh.…”
Section: Superconvergent Recovery By Element Patches (Epr1 and Epr2)mentioning
confidence: 99%
See 1 more Smart Citation
“…A more appropriate way of expressing M* over an element is by directly weighting the patch solution. 7 The error estimate (8) is used in the adaptive procedure to obtain an optimum mesh in which the error is equally distributed over the elements in a mesh; see Reference 8.…”
Section: The Superconvergent Patch Recovery and Error Estimationmentioning
confidence: 99%